The Influence of Transformational Leadership on Teaching Performance and Subjective Well-being of Lecturers - Agnes Renostini Harefa; Nathanael Sitanggang; Elizon Nainggolan (Universitas Pendidikan Ganesha, 2022)
Improving the quality of education cannot be done partially but must be comprehensive and sustainable. A capable leader is needed to improve the quality of education in schools. This research aims to analyze the effect of transformational leadership on teaching performance. This type of research is quantitative by using quantitative methods. Respondents in this study were permanent lecturers in the Teaching and Education Faculty, totaling 62 people. Data collection was carried out by distributing closed questionnaires to the respondents. The data analysis technique uses SPPS 25 analysis. Namely, the data that has been collected is analyzed quantitatively using path analysis, then proceed with a qualitative description to obtain a clearer picture of the results. This study's results indicate no significant effect of transformational leadership on the teaching performance of lecturers. These results suggest that the variable Transformational leadership has no significant effect on Lecturer Teaching Performance. Transformational leadership has no significant impact on the subjective well-being of lecturers. These results conclude that in structural II regression, the variable Transformational Leadership (X) has no significant effect on the Lecturer's Subjective Well-being (Y2). These results conclude that in structural II regression, the variable Lecturer Teaching Performance (Y1) has no significant effect on Lecturer Subjective Well-being (Y2).